PENGGUNAAN MODEL PEMBELAJARAN PROBLEM SOLVING KOOPERATIF TERHADAP PEMAHAMAN KONSEPTUAL DAN ALGORITMIK MAHASISWA PADA POKOK BAHASAN - Yudha Irhasyuarna (Universitas Lambung Mangkurat, 2013)
This research is made with aim to understand: (1) the difference in student’s conceptual understanding between problem solving cooperative learning model and conventional learning model in thermodynamic, (2) the difference student’s algorithmic understanding between problem solving cooperative learning model and conventional learning model in thermodynamic. This research is made by using quasiexperiment method which using pretest post-test nonequivalen control group design. The design of nonequivalen control group is used because random aspect can’t be filled perfectly, caused by difficulty in choosing and arranging the members of control group and experiment group. In this research, two class groups determined as research sample. One is for experiment group, which using problem solving model, and one is for control group which using conventional learning model. The instruments that developed in this research are multiple choice with reason, questionnaire, and observation sheet. The data analysis techniques that used in this research are descriptive analysis and analysis of covariant (Anacova). The research results conclude that: (1) student’s conceptual understanding, which using problem solving cooperative learning model, is higher than conventional learning, (2) student’s algorithmic understanding, which using problem solving cooperative learning model, is higher than conventional learning.Key words: problem solving, cooperative learning, conceptual understanding, algorithmic.